Double Sperm Cloning: Could Improve the Efficiency of Animal Cloning - Kumar, Dharmendra; Punetha, Meeti; Bansal, Sonu; Saini, Sheetal; Kumar, Pradeep; Sharma, R K; Yadav, P S (Animal Reproduction Update, 2022)
Somatic cell nuclear transfer (SCNT) is an assisted reproductive technology that produces an individual from a single somatic cell nucleus and an enucleated oocyte. SCNT has presented an extensive application in the multiplication of superior germplasm, production of transgenic animals, the rescue of endangered animals, and therapeutic cloning. Despite that, the competence of SCNT remains very low due to poor reprogramming of somatic cells and epigenetic modifications. The somatic cells used in SCNT as donor nuclei lack some important components which normally present in sperm cells that are transmitted during fertilization. Sperm-derived factors play an important role in nucleus reprogramming during SCNT and embryonic development. Loss of such factors in somatic cells is reflected as an imperative reason for the abnormal development of SCNT embryos. To improve the efficiency of somatic cells’ nuclear reprogramming during SCNT, double sperm cloning (DSC) could be an alternative approach to produce clone embryos/animals. Here, we focus on the recent advances of SCNT and their bottleneck and explored the possibility of cloning efficiency using sperm as donor nuclei.